2022
DOI: 10.1111/infa.12496
|View full text |Cite
|
Sign up to set email alerts
|

Changes in selective attention to articulating mouth across infancy: Sex differences and associations with language outcomes

Abstract: ILS conducted main statistical analyses, contributed to interpreting the results, wrote the first draft and edited subsequent versions of the manuscript.DLP contributed to the pre-processing of eye-tracking data and commented on earlier versions of the manuscript.ZL contributed to the interpretation of the results and editing the manuscript.MS conducted statistical analyses and contributed to the coordination of the study.AR conducted statistical analyses and contributed to the coordination of the study. CHANG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 69 publications
2
5
0
Order By: Relevance
“…The results showed that infants vocalized more when their faces were upright, made eye contact, and when infants looked more at the speakers' mouths [48]. The correlation between mouth-looking and language skills has also been shown by other studies, albeit with differences in age and the specific aspects of lexical development (see [44,45]).…”
Section: Infants' Preference For Facessupporting
confidence: 74%
See 1 more Smart Citation
“…The results showed that infants vocalized more when their faces were upright, made eye contact, and when infants looked more at the speakers' mouths [48]. The correlation between mouth-looking and language skills has also been shown by other studies, albeit with differences in age and the specific aspects of lexical development (see [44,45]).…”
Section: Infants' Preference For Facessupporting
confidence: 74%
“…Prior studies have approached this question by exploring infants’ selective attention to videos of talking faces, analyzing their looking time to the internal features of a talker’s face (i.e., eyes and mouth) across development. Furthermore, some have examined how such measures of attention relate to infants’ concurrent and later language outcomes, providing correlational evidence that attending to the eyes or the mouth region of a talking face at different stages of development can support language learning (e.g., [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ]).…”
Section: The Role Of Faces In Infants’ Attention and Language Acquisi...mentioning
confidence: 99%
“…The results showed that infants vocalized more when faces were upright, made eye-contact, and when infants looked more at the speakers' mouth [85]. The correlation between mouth-looking and language skills has also been shown by other studies, albeit with differences in the ages and specific aspects of lexical development (see [66], [70]).…”
Section: Infant' Attention To the Eyes And Mouth Of A Talking Face An...supporting
confidence: 74%
“…This is a different situation as compared to what happens in most of the studies that have examined the role of talking faces for language learning during infancy using screen-based tasks. Indeed, in virtually all these studies (including some work from the co-authors), non-contingent face-stimuli appear often exaggerated in size, and presented against a rather neutral background, with no or very few distractors on a computer screen (e.g., [62], [64], [66], [67], [69], [72], [74], [82]. Here, we argue that these presentation characteristics could lead to a distortion of the perceptual saliency of talking faces and their role in guiding infants' attention and language processing and learning.…”
Section: The Role Of Faces In Infants' Attention and Language Acquisi...mentioning
confidence: 99%
“…Longer looking to the mouth area of articulating face was observed in infants during the perception of McGurk stimuli in comparison to the congruent native speech stimuli (Mercure et al., 2019). Such increased visual attention to the mouth has been considered in the literature as an index of mature scanning patterns, related to speech perception development (Lewkowicz & Hansen‐Tift, 2012; Lozano et al., 2022; Morin‐Lessard et al., 2019). Mercure and collaborators (2019) concluded that longer fixations to the articulating mouth in younger infants (6.5‐ and 8‐month‐olds) in the incongruent condition may be due to novelty or surprise effect.…”
Section: Discussionmentioning
confidence: 99%